Borges/Xul Solar: Shared readings and divergent productions - Carricaburo, Norma Beatriz (2011)
Borges and Xul Solar were interested in the Holy Scriptures, in Kabbalah, Sufism, Brahamanism, Buddhism and in the cosmological, philosophical and ethical approaches of other thinkers, as Swedenborg and Blake. Borges often remembered the shared readings with Xul Solar. But even if they shared these readings, they came to very different findings.